Comparative Analysis of Hematological and Biochemical Changes in Neonates among Women with and without COVID-19 Infection during Pregnancy - Daniela-Eugenia Popescu; Simona Cerbu; Ioana Rosca; Nicoleta Lungu; Ana Adriana Trușculescu; Valerica Belengeanu; Aniko Maria Manea; Mirabela Adina Dima; Florin Gorun; Zoran Laurentiu Popa; Doru Ciprian Crisan; Marioara Boia (Children, 2023)
The aim of this study is to evaluate the test results of neonates delivered by COVID-19-positive mothers during pregnancy with those of neonates born to unvaccinated mothers who are COVID-19-free. A cohort study was conducted on 367 pregnant women who gave birth at Premiere Hospital, Timisoara, Romania, between May 2021 and February 2022. Two groups were established: Group 1, with 167 pregnant women infected with COVID-19, and Group 2, with 200 pregnant women who were not affected by COVID-19 during pregnancy. Maternal laboratory examination did not exhibit significant variations except for platelet count. In neonatal blood tests, WBC had a significantly lower median value in the group born to COVID-19-free mothers. Neonatal anemia and leukocytosis showed slightly higher prevalence in Group 1, but the differences were not statistically significant. This study suggests that maternal COVID-19 infection during pregnancy does not have significant associations with most maternal and neonatal characteristics.